Perempuan Dalam Hukum Keluarga Islam; Zakir Naik Perspektif - Zulfikar (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
Zakir Naik is a popular figure who has contributed to his thoughts on women in Islamic Family Law. This paper aims to describe Zakir Naik's perspective on Islamic Family Law regarding women. This paper is the result of normative legal research in the field of Islamic Family Law using a conceptual approach. The primary legal material in this research is Zakir Naik's book entitled; “Right of Women in Islam, Modern or Outdated” and “Most Common Questions Asked by Non-Muslims” and a number of other books. The technique of collecting data from primary legal materials is carried out thematically. Furthermore, in analyzing the data used content analysis method. The results of the study conclude that Islamic Family Law according to Zakir Naik has given rights to women fairly and proportionally, directly proportional to the roles and responsibilities that must be carried out; both roles as wife, mother and as children. In her role as a wife, women are given the right to accept or reject their future husband. Besides, women as wives are given the right to accept or reject polygamy by their husbands. In their role as mothers, women are given the right to be respected, cared for and loved by their children with a share of 75% compared to fathers.